Relationship between household air pollution and lung cancer in never smokers in high-income countries: a systematic review - Sam Khan; Karen Brown; Selina Lock; Samuel Cai; Bría Joyce McAllister; Rushad Malhotra Mukhtyar (BMJ Open)
Objectives Lung cancer is increasingly being diagnosed in non-smokers, with mounting evidence that household air pollution is a potential factor. Environmental risk factors for lung cancer in never-smokers (LCINS) in relation to combustion of biomass for heating and cooking in low-middle-income countries (LMICs) have been extensively explored. However, such evidence in high-income countries (HICs) is limited. We conducted a systematic review to explore potential relationships between exposure to cooking fumes, a type of household air pollution, and lung cancer, specifically in relation to never-smokers in HICs.Design Systematic review and narrative synthesis using the Critical Analysis Skills Programme (CASP) guidelines for case–control studies.Data sources Embase, Scopus, the Cochrane library and CINAHL were searched, from inception to March 2024. Reference lists of articles were hand searched for additional papers.Eligibility criteria Case–control studies focusing on household air pollution and its impact on LCINS in HICs were included.Data extraction and synthesis Two independent reviewers searched, screened and coded included studies using a bespoke table. Quality of evidence was assessed in the selected studies using the CASP tool for case–control studies. Retained studies used different exposure assessment and reporting methods which were sufficiently heterogeneous to preclude meta-analysis; therefore, narrative synthesis was performed.Results Three papers were included, with a total of 3734 participants. All studies were conducted in Taiwan or Hong Kong, focusing on Chinese women using traditional Chinese cooking methods. All three found a dose/response correlation between exposure to cooking fumes and the risk of developing LCINS.Chen et al assessed the risk of lung cancer risk by ‘cooking time-years’, measuring exposure to cooking fumes over a participant’s lifetime, citing OR 3.17 (95% CI 1.34 to 7.68) for the highest levels of exposure. Yu et al used ‘cooking dish-years’ as a measure of exposure to cooking fumes, with OR 8.09 (95% CI 2.57 to 25.45) for the highest exposure levels, while Ko et al found that the number of dishes cooked daily was a greater indicator of risk than the number of cooking years, citing a threefold increased risk of lung cancer among women who cooked three meals per day compared with those who cooked one (OR 3.1, 95% CI 1.6 to 6.2).Ventilation hoods were found to have a protective effect against LCINS with adjusted ORs of 0.49 (95% CI 0.32 to 0.76).Conclusions This review of three studies found a possible association between exposure to cooking fumes and the risk of developing LCINS in high-income settings. This corroborates the substantial body of evidence that links cooking fume exposure to LCINS in LMICs, with definitive confirmation of the exposure hazards.PROSPERO registration number CRD42024524445.